A reconstruction of Carroll's pyramid of corporate social responsibility for the 21st century - Denise Baden (International Journal of Corporate Social Responsibility (JCSR), 2016)
As one of the most influential models of corporate social responsibility (CSR), Carroll's pyramid of CSR has both reflected, and helped to perpetuate, a business-centric notion of CSR which implies that economic responsibilities take precedence over legal and ethical responsibilities. This paper argues that this conception of CSR needs updating to reflect the increased power of business in society. An empirical survey of 400 respondents from both business and non-business backgrounds indicated that current conceptions of the relative importance of business responsibilities differ greatly from Carroll's rankings. Based on the empirical research and conceptual arguments, a revised CSR pyramid is proposed with responsibilities ranked as follows: ethical, legal, economic and philanthropic.
Keywords: 650; Business ethics; Carroll; Corporate social responsibility; Philanthropy; Pyramid of CSR